Pengaruh Faktor Budaya, Sosial, dan Pribadi terhadap Keputusan Pembelian pada Industri E-Commerce (Shopee) di Politeknik Negeri Medan - Roito Marbun; Anggiat Parlindungan; Lily Maryam Nst; Nursiah Fitri; Indra Siregar (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Currently, the problem of consumer behavior is the low level of consumer awareness of the needs of the goods they buy. Some consumers admit that the goods they buy are not what they really need, but they still make purchases. There are also those who reveal that they order goods on the marketplace just because they are visually tempted. This certainly contradicts the purchasing decision theory which explains that the higher the consumer's awareness of the need for the goods needed, the higher the purchasing decision will be, and vice versa. This research aims to analyze the influence of cultural factors, social factors and personal factors on purchasing decisions. The approach used in this research is a quantitative method. The sampling technique used simple random sampling with a total of 99 respondents, who were users of the Shopee application. Data was collected via an online questionnaire and processed using SPSS with multiple regression data analysis techniques. The results of this research show that simultaneously, cultural, social and personal variables have a significant and positive influence on purchasing decisions, as indicated by the significant value of the F test < sig value, namely <,0.001 < 0.05. And partially, social and personal variables have a significant and positive influence on purchasing decisions, which is aimed at the significance value of the t test for each variable < sig value, namely (0.005 and <0.001 < 0.5). Meanwhile, cultural factors are rejected which is aimed at the significance value of the t test variable > sig value, namely (0.132 > 0.05). They feel that although communities such as those for music lovers, gamers, or fashion can be a forum for sharing the same interests, not everyone feels the need or is interested in being active in the online environment in discussions or activities within it.